2015
DOI: 10.1051/0004-6361/201424829
|View full text |Cite
|
Sign up to set email alerts
|

New data support the existence of the Hercules-Corona Borealis Great Wall

Abstract: Context. Several large structures, including the Sloan Great Wall, the Huge Large Quasar Group, and a large gamma-ray burst cluster referred to as the Hercules-Corona Borealis Great Wall, appear to exceed the maximum structural size predicted by Universal inflationary models. The existence of very large structures such as these might necessitate cosmological model modifications. Aims. Gamma-ray bursts are the most luminous sources found in nature. They are associated with the stellar endpoints of massive stars… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
89
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 20 publications
(24 reference statements)
3
89
1
1
Order By: Relevance
“…Both areas are in the same quadrant on the sky and they partially overlap. This finding is also interesting considering that Horváth et al (2014); Horváth et al (2015) used completely different approach and they studied number densities of GRBs on the sky for various redshift intervals employing a data set from a different satellite.…”
mentioning
confidence: 92%
See 3 more Smart Citations
“…Both areas are in the same quadrant on the sky and they partially overlap. This finding is also interesting considering that Horváth et al (2014); Horváth et al (2015) used completely different approach and they studied number densities of GRBs on the sky for various redshift intervals employing a data set from a different satellite.…”
mentioning
confidence: 92%
“…Recently, Horváth et al (2014); Horváth et al (2015) studied the spatial distribution of GRBs taking into account their redshift. They concluded that there was a statistically significant clustering of GRBs at redshift 1.6 < z ≤ 2.1 and that the size of the structure defined by these GRBs was about 2 000-3 000 Mpc, so called Hercules-Corona Borealis Great Wall.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Lately, with the help of multi-and uni-variate statistical analysis techniques an intermediate group was found [3,4,5,6,7,8,9,10,11,12,13]. Furthermore, recent publications have discovered large structures based on GRBs: the HerculesBorealis great wall at z ≈ 2 [14,15] and the Giant GRB ring at z ≈ 0.8 [16,17]. More GRBs with known redshift are necessary to understand the genesis of these structures.…”
Section: Introductionmentioning
confidence: 99%